2007
DOI: 10.1080/00016340701207682
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fetal growth is associated with gestational diabetes mellitus later in life: population‐based register study

Abstract: Intrauterine conditions and/or genetic disposition, which affect prenatal growth, increase the future risk of the female fetus developing GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
1
21
1
2
Order By: Relevance
“…This study strengthens previous findings of increased risk of pregnancy complications in women born with low birth weights. 6,[8][9][10][11][12] An inverse relation between birth weight and risk of preeclampsia and of gestational diabetes has been shown in case-control and populationbased cohort studies. 8,21,22 In a large populationbased cohort study, Zetterström and colleagues 10 found an increased risk of preeclampsia among women born small for gestational age (v. appropriate weight for gestational age).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study strengthens previous findings of increased risk of pregnancy complications in women born with low birth weights. 6,[8][9][10][11][12] An inverse relation between birth weight and risk of preeclampsia and of gestational diabetes has been shown in case-control and populationbased cohort studies. 8,21,22 In a large populationbased cohort study, Zetterström and colleagues 10 found an increased risk of preeclampsia among women born small for gestational age (v. appropriate weight for gestational age).…”
Section: Discussionmentioning
confidence: 99%
“…We performed normal logistic regressions using the 3 gestational age groups to obtain adjusted ORs and 95% confidence intervals (CIs). This analysis was done to distinguish the effect of preterm birth from the impact of confounding variables shown to be associated with increased risk of the pregnancy complications studied: small for gestational age and large for gestational age, 8,10 multiple pregnancy, maternal age of 25 years or older, 18 diagnosis of chronic hypertension, type 1 or 2 diabetes, and kidney disease. 19 The analyses were realized for (a) the risk of a pregnancy complication at least once during the study period (with the number of women affected as the unit of measurement and not the number of episodes; e.g., a woman with 3 pregnancies complicated by preeclampsia was included as 1 participant) and for (b) the risk of a pregnancy complication at the first live delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the baby is female, exposure to maternal hyperglycaemia in utero might increase her own risk of subsequently developing GDM in her own pregnancies [6]. Shortly after delivery, the glucose values are generally restored to normal, but women with GDM have a sevenfold increased risk of developing T2DM [7].…”
Section: Introductionmentioning
confidence: 99%
“…Bebek kız ise, gebelik sırasında maternal hiperglisemiye maruziyet onun da kendi gebeliklerinde GDM gelişmesi riskini artırır. Gebelik sırasındaki bu metabolik programlama tüm dünyada hızlı bir artış gösteren tip 2 DM prevalansı üzerine kuşaklar arası bir etki oluşturuyor olabilir (29).…”
Section: Fetal Ve Maternal Etki̇leri̇unclassified